2020
DOI: 10.3390/healthcare8030207
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Health Information Sharing Behavior of Chinese Elderly Adults on WeChat

Abstract: WeChat has increasingly become an important platform for users to acquire and share health information in China. However, little is known about elderly adults’ sharing behavior. This study aims to explore the characteristics and influencing factors of health information sharing behavior among Chinese older adults on WeChat, with the method both of questionnaire survey (N = 336) and in-depth interviews (N = 40). The study finds that sharing health information, mainly represented by four specific methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 53 publications
1
37
1
1
Order By: Relevance
“…In an attempt to capture WeChat users’ behaviors across different user groups, the survey company was requested to recruit an equal gender ratio, which largely reflects the current internet users’ gender structure in mainland China [ 15 ]. In addition, considering that Chinese elderly adults are found to be active in online health-related information engagement [ 43 , 81 ], the survey company was requested to particularly recruit more senior participants aged 50 years and above, although such an older population is relatively scarce in online panels in China. The survey company used several tactics in the process of administering the questionnaires to eliminate invalid cases (e.g., attention-check questions, detection of repeat Internet Protocol [IP] addresses, and surveillance).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In an attempt to capture WeChat users’ behaviors across different user groups, the survey company was requested to recruit an equal gender ratio, which largely reflects the current internet users’ gender structure in mainland China [ 15 ]. In addition, considering that Chinese elderly adults are found to be active in online health-related information engagement [ 43 , 81 ], the survey company was requested to particularly recruit more senior participants aged 50 years and above, although such an older population is relatively scarce in online panels in China. The survey company used several tactics in the process of administering the questionnaires to eliminate invalid cases (e.g., attention-check questions, detection of repeat Internet Protocol [IP] addresses, and surveillance).…”
Section: Methodsmentioning
confidence: 99%
“…The reason we focused on health information engagement was twofold. First, recent studies have found that WeChat is a promising platform for health communication, and users’ health-related information acquisition and engagement pervade the site (e.g., [ 81 , 86 88 ]). Indeed, mobile social media have become popular as a source of health information and provide active environments for health education and promotion due to its capacity for interactivity [ 45 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the online sources of RDs in China are scarce; in this study, over 60% of respondents noted a general lack of available information, not to mention the questionable reliability of such information. The dominant platform for seeking and exchanging information (including experiences and knowledge) about RDs in the current studies are virtual patient communities organized based on Electronic Bulletin Boards (or BBS) or social network gadgets (such as QQ or WeChat) [ 20 , 21 ]. However, such online communities are often closed and focus on one particular rare condition, which inevitably makes it hard for those with an ambiguous or unconfirmed diagnosis to join and find further help.…”
Section: Discussionmentioning
confidence: 99%
“…However, the online sources of RDs in China are scarce; in this study, over 60% of respondents noted a general lack of available information, not to mention the questionable reliability of such information. The dominant platform for seeking and exchanging information (including experiences and knowledge) about RDs in the current studies are virtual patient communities organized based on Electronic Bulletin Boards (or BBS) or social network gadgets (such as QQ or WeChat) [20,21]. However, such online communities are often closed and focus on one particular rare condition, which inevitably makes it hard for those with an ambiguous or uncon rmed diagnosis to join and nd further help.…”
Section: Discussionmentioning
confidence: 99%